PENGARUH PENDIDIKAN KESEHATAN TERHADAP SIKAP DAN PEMANFAATAN SENAM LANSIA DI WILAYAH POSYANDU LANSIA RW.03 DESA GEMBLEGAN KALIKOTES KLATEN - Kristiningtyas, Y. Wahyunti; Purwandari, Kristiana Puji (Akademi Keperawatan Giri Satria Husada Wonogiri, 2021)
Background: Elderly (elderly) is a human life cycle that almost everyone experiences. The older you get, the more likely a person is to experience physical, mental, spiritual, economic and social problems. One of the very basic problems is health problems due to degenerative processes. One of the efforts to maintain, improve health and physical fitness for the elderly is to do sports that have benefits for maintaining health. Health promotion aims to raise awareness, provide or increase public knowledge about maintaining and improving health for themselves, their families and the community. The expected result of a health promotion or education is health behavior, or behavior to maintain and improve conducive health. Objective: The purpose of the study was to determine the effect of health education on the attitudes and use of elderly gymnastics in the elderly posyandu area RW.03 Gemblegan Village, Kalikotes Klaten. Methods: This research is a type of pre-experimental research with One Group Pre-test and Post-test designs. The research population of all the elderly in the elderly posyandu area of RW.03 was 71 people. The number of samples is 60 elderly. Sampling technique with simple random sampling. The instrument is a questionnaire regarding the attitude and use of elderly exercise. Data analysis is univariate and bivariate analysis with Mc Nemar test. Result: Attitude variable shows p value = 0.0001 which is smaller than 0.05, which means that there is an effect of providing health education on the attitude of the elderly about elderly exercise. The variable for the use of elderly gymnastics shows p value = 0.0001 which is smaller than 0.05, which means that there is an effect of providing health education on the use of elderly gymnastics in the Posyandu area for the elderly, RW.03, Gemblegan Village.